Clitic-verb non-adjacency and the inertial theory of grammatical change: evidence from the history of European Portuguese - Nkollo, Mikołaj (Lingua Posnaniensis, 2019)
Although clitic-verb non-adjacency is a minor linear pattern in contemporary European Portuguese (EP), it showed a significant frequency in the Classical and early Modern eras. The aims of the study are twofold. First, an attempt is made to pinpoint the contribution of the cl-X-verb model to the non-morphological attachment of proclitics to their verbal hosts in present-day EP. By means of a corpus analysis conducted in the 17th through 19th century texts, clitic-verb non-adjacency is demonstrated to have helped eliminate clitic -specific allomorphy in the preverbal domain. Its precise role consisted in preventing proclitics from being integrated into their hosts. The second aim is to see how this diagnosis fits in with the inertial model of grammatical change. In line with Longobardi’s proposal (2001), innovation in the syntactic processing of preverbal pronouns is claimed to have come about as a side-effect of the changes in more peripheral modules of grammar, i.e. in phonology and morphology.